2014
DOI: 10.1080/23273798.2014.942326
|View full text |Cite
|
Sign up to set email alerts
|

Multi-level processing of phonetic variants in speech production and visual word processing: evidence from Mandarin lexical tones

Abstract: Two picture-word interference experiments provide new evidence on the nature of phonological processing in speech production and visual word processing. In both experiments, responses were significantly faster either when distractor and target matched in tone category, but had different overt realisations (toneme condition) or when target and distractor matched in overt realisation, but mismatched in tone category (contour condition). Tone 3 sandhi is an allophone of Beijing Mandarin Tone 3 (T3). Its contour i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 51 publications
(56 reference statements)
4
28
1
Order By: Relevance
“…In Beijing Mandarin, Tone 3 (T3) has at least two variants. T3 usually has a low contour, but preceding another T3 syllable, it is realised with a rising contour (sandhi T3).Importantly for the present study, the contour of sandhi T3 is very similar to another tone, Tone 2.A previous study (Nixon, Chen & Schiller, 2015) showed that production and visual processing of Mandarin tonal variants involves multi-level phonological processing, where there is activation of both the tonal contour and the tone category. The present study investigates whether the context provided by the following character in briefly presented masked primes affects processing of tone during reading aloud.…”
Section: Introductionsupporting
confidence: 53%
“…In Beijing Mandarin, Tone 3 (T3) has at least two variants. T3 usually has a low contour, but preceding another T3 syllable, it is realised with a rising contour (sandhi T3).Importantly for the present study, the contour of sandhi T3 is very similar to another tone, Tone 2.A previous study (Nixon, Chen & Schiller, 2015) showed that production and visual processing of Mandarin tonal variants involves multi-level phonological processing, where there is activation of both the tonal contour and the tone category. The present study investigates whether the context provided by the following character in briefly presented masked primes affects processing of tone during reading aloud.…”
Section: Introductionsupporting
confidence: 53%
“…It is widely accepted that lexical tones function as abstract lexical frames and prosodic cues in the mental representation of words (Chen, Chen, & Dell, 2002;Ye & Connine, 1999), similarly to lexical stresses (Cutler & Van Donselaar, 2001;Cutler, 1986;Jongenburger, 1996;Levelt, Roelofs, & Meyer, 1999;Van Heuven, 1988), and that tonal minimal pairs have distinct representations in lexical access (Chen, Shen, & Schiller, 2011;Malins & Joanisse, 2010Nixon, Chen, & Schiller, 2014;Wu, Chen, Van Heuven, & Schiller, 2014). Bilinguals of two tonal languages access tonal information differently than those who use only one (Wiener & Ito, 2015).…”
Section: Tonal Bilingualism Of Two Chinese Mandarin Dialectsmentioning
confidence: 99%
“…Chinese compounds also contain a number of prosodic information, such as lexical tones and tone sandhi. Previous studies have shown that both tone category and tonal contour are activated during speech production (Nixon, Chen, & Schiller, 2015). During spoken word recognition, listeners may use the prosodic information to select a morpheme correctly, thereby facilitating early lexical decomposition.…”
Section: Discussionmentioning
confidence: 99%